Energy levels of Pd 106 fed in the Rh 106m decay - Yuthman de Aisenberg, E.; Suarez, J. F. (North Holland Publishing, 1966)
Fil: Yuthman de Aisenberg, E. Comisión Nacional de Energía Atómica; Argentina